Motor synchrony, social learning and closeness in group play settings - Nguyen, Trinh; Tunçgenç, Bahar; Marsh, Lauren; Markova, Gabriela; Horn, Lisa; Pointner, Nadine; Schleihauf, Hanna; Hoehl, Stefanie (Frontiers in psychology, 2025)
IntroductionPlayful activities provide critical opportunities for rhythmic interactions, which may affect social and cognitive development in early childhood. Prior research suggests that motor synchrony promotes closeness and prosocial behaviour, but few studies have examined its role in social learning and in group settings.MethodThis study investigated whether motor synchrony in a clapping game, enhances preschoolers' closeness with others, imitation, over-imitation, and sharing behaviour. In a group setting, motor synchrony and asynchrony were experimentally induced between the child and two experimenters. We hypothesized that children would feel closer, imitate more, and share more with an adult partner who moved in synchrony compared to one who moved asynchronously.ResultsBayesian analyses revealed no credible evidence that the children affiliated, imitated, over-imitated, or shared differently with their synchronous vs. asynchronous partner (BF10 = 0.045-0.216). Manipulation checks indicated that although the adults adhered to the stimuli, there was overall low motor synchrony.DiscussionThese findings highlight the challenges of inducing motor synchrony in playful group settings and raise questions about the level of synchrony necessary to impact social affiliation and learning in young children.